Berlinia grandiflora Hutch and Dalz Ethanol Stem Bark Extract Ameliorates the Effect of CCl\(_4\) Induced Liver Damage in Rats - Donkor, Martin Ntiamoah; Donkor, Addai-Mensah (Pharmaceutical Research: Recent Advances and Trends Vol. 10, 2024)
The largest organ in the body, the liver, serves as the final organ in biological processes like metabolism, excretion, and detoxification. Hepatocytes are destroyed throughout the procedure, which might lead to problems or liver damage. The objective of the present study was to provide empirical support for the folkloric assertion that the stem bark of Berlinia grandiflora is utilized in the treatment of hepatic disorders. This was achieved by evaluating the effect of the ethanol extract on liver maker enzymes in vivo. Six groups of six Wistar albino rats were selected and each was subjected to different treatments with carbon tetrachloride (CCl4), followed by ethanol stem bark Berlinia grandiflora extract (ESBG) for seven days. At the conclusion of the treatment period, serum biochemical parameters were evaluated to determine the health of the liver. Treatment of rats with ESBG (at doses 100, 300 and 900 mg/kg b.w., orally) reduced the impact of CCl4-induced hepatotoxicity on liver maker enzymes Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline phosphatase (ALP) and Total Bilirubin (TB), with the 900 mg/kg b.w. showing a significant reduction (p < 0.05) compared to the group treated with only CCl4. Serum Total protein (TP) and albumin (ALB) increased in rats treated with the extracts, with the 900 mg/kg b.w. dose showing a significant increment (p<0.05) compared to the group treated with only CCl4. The study revealed that the ethanol extract of Berlinia grandiflora stem bark was able to ameliorate the effect of CCl4-induced liver damage, thus supporting the traditional usage of the plant in treating liver-related disorders.